Developments in bioacoustics monitoring for management of marine mammal presence in shipping lanes - Ghate, Dr. Atul Dattatraya; Roy, Dr. Jainish; Negi, Gajendra Singh (International Journal of Aquatic Research and Environmental Studies, 2025)
Research assessing Marine Mammal (MM) health and prospects for enhancing the care of individuals in professional facilities has significantly escalated during the past decades. Although subjects like comfortable housing, sufficient opportunities for social and engaging enhancement, and superior medical treatment have garnered attention from management and researchers, there is a deficiency in defined acoustic parameters for assessing the welfare of these creatures. MM depend on bioacoustic (BA) emission and perception for orientation and interaction. Numerous countries have established regulations regarding artificially generated sounds in seas, primarily informed by studies with controlled and trained creatures, owing to the possible adverse effects of unregulated noise on MM. A definitive standard of excellence for the BA well-being tracking of marine creatures in medical facilities has yet to be developed. Measuring MM auditory perception and vocalization can provide a comprehensive understanding of MM health by facilitating the early identification of anthropogenic sounds, analyzing the BA activity of the livestock, and examining the characteristics of their calls. This review introduces and discusses the method of tracking cetacean BA social assistance through emotional hearing assessments and Auditory Evoked Possibilities (AEPs), inactive acoustic tracking devices like the Welfare Acoustic Monitoring Systems (WAMS), and proposes the application of novel methods for leveraging vocal health indicators as possibilities for incorporation into MM welfare strategies.